The influence of Packed Cells Volume (PCV) and Temperature on Erythrocytes Sedimentation Rate (ESR) - Baghdad Science Journal (مجلة بغداد للعلوم)
Erythrocytes aggregation is an important physiological phenomenon in the circulation of blood, and is a basic characteristic of normal blood that plays a major role in cardiovascular system especially in the microcirculation. Blood samples have been taken from (30) volunteers (15 male, and 15 female), their ages (20-30) years. The Erythrocytes Sedimentation Rate (ESR) for those subjects was measured at different Packed Cells Volume (PCV) (10%-25%), and also it was measured at different temperature (10oC-25oC). The results show that there was a highly significant decrease (P